A high-precision rolling process for rolled steel bars

By synthesising nano nickel particles on the surface of nano silicon carbide and using nitrogen-doped carbon nanosheets, the problem of water-based nanolubricants being prone to breakage and poor binding strength during the rolling process of steel rolling rods is solved, and the more Good lubrication effect and steel mechanical properties extend the roll life.

CN119060780BActive Publication Date: 2025-01-07ANHUI SHOUGANG DACHANG METAL MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411562997.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

When water-based nanolubricant is sprayed between the steel billet and the rolling mill, the nanoparticles tend to accumulate and cause the lubricating film to rupture, and the binding force is not firm, resulting in poor lubrication effect, which affects the surface quality of the rolled steel rod and the life of the rolling roll.

Method used

Synthesize nano nickel particles on the surface of nano-silicon carbide to form concave and convex structures to improve binding force, and use nitrogen-doped carbon nanosheets as nanoadditives for water-based nanolubricants to synthesize nanomolybdenum disulfide seals with fullerene-like structures Block porous structures, increase compactness and compressive strength, and coat modified nitrogen-doped carbon nanosheets with graphene oxide to provide stable slip space, phytic acid and thiosilane form a crosslinking network structure to reduce iron oxide generate.

Benefits of technology

It improves the toughness and mechanical properties of steel materials, provides better lubrication effect, reduces friction and roll wear, extends the service life of rolling rolls, and improves the quality of rolled steel rods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-precision rolling process for rolled steel bars, which belongs to the technical field of steel rolling. The preparation method comprises the following steps: mixing steel component raw materials and reinforcing fillers, smelting and refining, and then casting into steel billets; placing the steel billets in a hot rolling mill, spraying water-based nano-lubricants, and hot rolling to obtain rolled steel bars. The steel matrix can penetrate into the gaps of the concave-convex structure on the surface of nano-silicon carbide, thereby improving the bonding force between the nano-silicon carbide and the steel matrix, and then forming a dense steel material; forming spherical nano-molybdenum disulfide on the surface of nitrogen-doped carbon nanosheets, producing a rolling lubrication effect, and reducing the friction between the steel billet and the rolling mill components during the rolling process; graphene oxide is on the upper and lower surfaces of the modified nitrogen-doped carbon nanosheets, providing a stable sliding space for the spherical nano-molybdenum disulfide on the surface of the modified nitrogen-doped carbon nanosheets, thereby preventing the spherical nano-molybdenum disulfide from peeling off from the nitrogen-doped carbon nanosheets during the friction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel rolling, in particular to a high-precision rolling process for rolled steel bars. Background Art

[0002] Rolled steel bars have the advantages of good mechanical properties, high temperature resistance, corrosion resistance, wear resistance, good sealing effect, etc. They have been widely used in military, machinery, manufacturing and other industrial fields. They not only have a positive role in promoting the automotive manufacturing industry and mechanical industry production, but also make a significant contribution to the development of the national economy. Rolled steel bars are rolled by rolling mills, which is a pressure processing method in which the steel billet passes through the gap between the rollers (various shapes) and the cross-section of the material is reduced and the length is increased due to the compression of the rollers. This is the most commonly used production method for rolled steel bars.

[0003] During the rolling process of steel bars, water is mostly used for cooling, which causes oxidation of the steel to form iron scale, which is easily pressed into the surface of the roller, resulting in periodic rolling marks, affecting the surface quality of the bars. In severe cases, the rollers are scrapped and the qualified rate of the rollers is reduced. The new high-temperature rolling lubrication technology can improve the surface quality and rolling efficiency of the rollers, reduce roller consumption and energy consumption, and has significant economic and social benefits.

[0004] Spraying water-based nanolubricant between the steel billet and the rolling mill roll forms a lubricating film on the rolling mill roll, which can effectively reduce friction. However, the aggregation of nanoparticles in the water-based nanolubricant can easily lead to the rupture of the lubricating film during the rolling process. In addition, the lubricating film formed between the water-based nanolubricant and the rolling mill roll has weak bonding and is easy to fall off, resulting in poor lubrication effect. Summary of the invention

[0005] The purpose of the present invention is to provide a high-precision rolling process for rolled steel bars: synthesizing nano-nickel particles on the surface of nano-silicon carbide, thereby forming a concave-convex structure on the surface of nano-silicon carbide, and the steel matrix can penetrate into the gaps of the concave-convex structure on the surface of nano-silicon carbide, thereby improving the bonding force between the nano-silicon carbide and the steel matrix, thereby forming a dense steel material; 4,4'-bipyridine and cupric chloride form a copper-pyridine complex as a nitrogen-carbon precursor, and the formed nitrogen-doped carbon nanosheets are used as nano-additives for water-based nano-lubricants, which can form a nano-lubricating film on the surface of a roller and provide a better lubricating effect; synthesizing nano-molybdenum disulfide with a fullerene-like structure on the surface of the nitrogen-doped carbon nanosheets to block the nitrogen-doped carbon nanosheets. The porous structure improves the density of the nitrogen-doped carbon nanosheets, thereby improving the compressive strength and avoiding the porous structure from being brittle and breaking during the rolling process; graphene oxide is coated on the upper and lower surfaces of the modified nitrogen-doped carbon nanosheets to provide a stable sliding space for the spherical nano-molybdenum disulfide on the surface of the modified nitrogen-doped carbon nanosheets, avoiding the spherical nano-molybdenum disulfide from being peeled off from the nitrogen-doped carbon nanosheets during the friction process, resulting in increased friction and affecting the lubrication effect; the cross-linked network structure formed by the mixture of phytic acid and mercaptosilane can complex with the iron ions in the iron oxide flakes easily produced by oxidation on the surface of the roller, reduce the generation of iron oxide, and avoid the formed iron oxide scale adhering to the surface of the roller and being pressed into the steel billet, affecting the quality of the rolled steel bar.

[0006] The technical problem to be solved by the present invention is as follows: spraying a water-based nano-lubricant between the steel billet and the rolling mill roll to form a lubricating film on the rolling mill roll, which can effectively reduce the friction. However, the aggregation of nanoparticles in the water-based nano-lubricant can easily lead to the rupture of the lubricating film during the rolling process. In addition, the lubricating film formed between the water-based nano-lubricant and the rolling mill roll has a weak bonding force and is easy to fall off, resulting in poor lubrication effect.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A high-precision rolling process for rolled steel bars comprises the following steps:

[0009] S1. The steel component raw materials and reinforcing fillers are mixed, smelted into molten iron, refined, and cast into steel billets.

[0010] S2. placing the steel billet in a hot rolling mill, spraying a water-based nano-lubricant, and obtaining a rolled steel bar after hot rolling.

[0011] Furthermore, the steel component raw materials contain 0.22-0.27% carbon, 0.22-0.25% silicon, 1.4-1.5% manganese, 0.02-0.03% chromium, 0.006-0.008% molybdenum, 0.007-0.009% nickel and the balance is iron and inevitable impurities.

[0012] Furthermore, the mass ratio of steel component raw material and reinforcing filler is (90-100):(0.8-1).

[0013] Furthermore, the smelting temperature is 1200-1280°C, and the smelting time is 3-5h.

[0014] Furthermore, the pouring temperature is 800-1050°C, and the pouring time is 2-3h.

[0015] Furthermore, the hot rolling mill is selected from a two-roll experimental hot rolling mill, and the diameter of the two rolls is 225-254 mm.

[0016] Furthermore, the hot rolling treatment temperature is 800-900° C., and the hot rolling speed is 0.3-0.6 m / s.

[0017] Furthermore, the spraying temperature is 120-150° C., and the spraying time is 1-2 min.

[0018] Furthermore, the reinforcing filler is prepared by mixing nano silicon carbide and a nickel source, subjecting the mixture to a thermal reduction reaction, and then depositing the mixture onto the surface of the carbon fiber.

[0019] Further, the nickel source is selected from nickel nitrate hexahydrate or nickel chloride.

[0020] Furthermore, the carbon fiber has a diameter of 0.1-2 μm and a diameter of 30-50 nm.

[0021] Furthermore, the particle size of nano-silicon carbide is 40-60nm.

[0022] Furthermore, the thermal reduction reaction temperature is 450-500°C, and the thermal reduction reaction time is 1-3h.

[0023] Further, the reinforcing filler is specifically prepared by the following steps:

[0024] A1. Add nano-silicon carbide to a Tris-HCl buffer solution with a pH of 8, stir evenly, add dopamine, stir at room temperature for 3 hours, filter, wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain pretreated nano-silicon carbide.

[0025] Among them, dopamine can self-polymerize on the surface of nano-silicon carbide to form a polydopamine layer, so that dopamine adheres to the surface of nano-silicon carbide, giving excellent adhesion, and can adhere nickel ions in the nickel source to the surface of nano-silicon carbide, which is beneficial to the synthesis of nano-nickel particles on the surface of nano-silicon carbide.

[0026] Furthermore, the dosage ratio of nano-silicon carbide, Tris-HCl buffer solution, and dopamine is (0.3-0.7) g: (40-50) mL: (0.2-0.4) g.

[0027] A2. Add nickel source to ethanol, stir evenly, add pretreated nano-silicon carbide, stir at 25°C for 10 minutes, stir at 75°C to remove ethanol, dry in a 70°C oven for 10 minutes, place in a tube furnace, heat to 500°C, pass 20% argon-hydrogen mixed gas, perform thermal reduction for 2 hours, cool to room temperature, and obtain modified nano-silicon carbide.

[0028] Among them, the polydopamine layer contained in the surface of the pretreated nano-silicon carbide has excellent adhesion, and can deposit nickel ions in the nickel source on the surface of the nano-silicon carbide. At 500°C, an argon-hydrogen mixture is used as a reducing agent to reduce the nickel ions to nano-nickel with a particle size of 20-30nm, thereby realizing the synthesis of nano-nickel on the surface of the nano-silicon carbide, and then forming a concave-convex structure on the surface of the nano-silicon carbide, increasing the contact area with the steel material, so that the reinforcing filler formed by the nano-silicon carbide particles can be evenly dispersed in the molten steel.

[0029] Furthermore, the usage ratio of nickel source, ethanol, and pretreated nano-silicon carbide is (1-2) g: (45-55) mL: (0.2-0.4) g.

[0030] A3. Place the carbon fiber in a 58% nitric acid aqueous solution, stir at 60°C for 1 hour, take out, wash and dry to obtain pretreated carbon fiber, add modified nano silicon carbide and γ-aminopropyltriethoxysilane to ethanol and deionized water, stir evenly, add 36% hydrochloric acid by mass to adjust the pH to 4, stir and react at 40°C for 10 minutes, add the pretreated carbon fiber, continue to react for 10 minutes, filter, wash and dry to obtain reinforcing filler.

[0031] Among them, the carbon fiber is placed in an aqueous nitric acid solution and is oxidized so that the surface of the carbon fiber carries a large number of carboxyl functional groups; the hydroxyl group carried by the nano-nickel on the surface of the modified nano-silicon carbide can react with the hydroxyl group produced by the hydrolysis of γ-aminopropyltriethoxysilane, so that the modified nano-silicon carbide carries the reactive group amino group, and under acidic conditions (provided by hydrochloric acid), the amino group carried by the modified nano-silicon carbide can react with the carboxyl group on the surface of the pretreated carbon fiber, so that the modified nano-silicon carbide is deposited on the surface of the carbon fiber.

[0032] Furthermore, the usage ratio of carbon fiber and nitric acid aqueous solution is (0.3-0.7) g: (25-35) mL.

[0033] Furthermore, the usage ratio of modified nano silicon carbide, γ-aminopropyltriethoxysilane, ethanol, deionized water, hydrochloric acid, and pretreated carbon fiber is (0.1-0.3) g:(0.4-0.5) g:(10-14) mL:(1-3) mL:(0.1-0.3) mL:(0.3-0.5) g.

[0034] Furthermore, the water-based nano-lubricant comprises the following raw materials in parts by weight: 2-4 parts of nano-lubricating filler, 10-12 parts of glycerol, 0.2-0.3 parts of sodium dodecylbenzene sulfonate, and 80-120 parts of deionized water.

[0035] Furthermore, the water-based nano-lubricant is prepared by the following steps:

[0036] The nano-lubricating filler, glycerol, sodium dodecylbenzene sulfonate and deionized water are mixed and stirred evenly to obtain a water-based nano-lubricant.

[0037] Furthermore, the nano-lubricating filler is prepared by mixing a composite layered nano-material, phytic acid, and mercaptosilane, and stirring the mixture for reaction, and is specifically prepared by the following steps:

[0038] Phytic acid and mercaptosilane were added to deionized water, stirred and reacted at 50° C. for 30 minutes, the composite layered nanomaterial was added, stirred for 10 minutes, filtered, and dried in an oven at 80° C. for 10 minutes to obtain a nano-lubricating filler.

[0039] Among them, the hydroxyl groups produced by the hydrolysis of phytic acid and mercaptosilane react to form a cross-linked network structure, embedding the composite layered nanomaterials into the cross-linked network structure, improving the water solubility of the composite layered nanomaterials, and avoiding the agglomeration of the composite layered nanomaterials in the water-based system.

[0040] Furthermore, the dosage ratio of phytic acid, mercaptosilane, deionized water, and composite layered nanomaterial is (3-3.4) mL: (1-3) mL: (80-120) mL: (1-2) g.

[0041] Furthermore, the mercaptosilane is selected from 3-mercaptopropyltrimethoxysilane.

[0042] Furthermore, the composite layered nanomaterial is prepared by mixing nitrogen-doped carbon nanosheets with a molybdenum-sulfur source, heat-treating the mixture, and then mixing it with graphene oxide.

[0043] Furthermore, the molybdenum-sulfur source is selected from ammonium tetrathiomolybdate.

[0044] Furthermore, the heat treatment temperature is 750-850°C, and the heat treatment time is 1-3h.

[0045] Furthermore, the particle size of the nitrogen-doped carbon nanosheets is 200-300 nm;

[0046] Further, the graphene oxide particle size is 100-200 nm;

[0047] Furthermore, the composite layered nanomaterial is specifically prepared by the following steps:

[0048] B1. Place the nitrogen-carbon precursor in a carbonization furnace, carbonize at 500°C for 1 hour, cool to room temperature, take out, soak in 4 mol / L nitric acid for 24 hours, filter, wash with deionized water 3 times, and dry in an oven at 40°C for 1 hour to obtain nitrogen-doped carbon nanosheets.

[0049] Among them, the nitrogen-carbon precursor is carbonized at 500°C, so that the pyridine molecules in the nitrogen-carbon precursor are thermally decomposed to form a carbon layer. Furthermore, the release of hydrogen and nitrogen in the nitrogen-carbon precursor forms a porous structure on the surface of the carbon layer. During the release of nitrogen, nitrogen atoms are partially doped into the carbon layer to form nitrogen-doped carbon nanosheets. After the nitrogen-doped carbon nanosheets are etched with nitric acid, more oxygen-containing functional groups can be attached to the nanosheets, thereby improving the activity, which is conducive to the synthesis of spherical molybdenum disulfide on the surface of the nitrogen-doped carbon nanosheets.

[0050] Furthermore, the ratio of nitrogen-carbon precursor to nitric acid is (4-6) g:(45-55) mL.

[0051] B2. Add the molybdenum-sulfur source to N-methyl-2-pyrrolidone, stir evenly, heat to 80°C, stir for 2 hours, add hydrazine, continue stirring for 1 hour, add nitrogen-doped carbon nanosheets, stir evenly, apply negative pressure at -0.1MPa to allow the molybdenum-sulfur source to penetrate into the porous nanomaterial, soak for 10 hours, place in an 80°C oven to dry for 8 hours to evaporate the solvent, place in a tubular furnace at 800°C, pass nitrogen, heat treat for 2 hours, cool to room temperature, and obtain modified nitrogen-doped carbon nanosheets.

[0052] Among them, the oxygen-containing functional groups on the surface of the nitrogen-doped carbon nanosheets act as adsorption sites, which can combine with the molybdenum atoms in the molybdenum-sulfur source. Under a negative pressure of -0.1 MPa, the molybdenum-sulfur source penetrates into the pores of the nitrogen-doped carbon nanosheets and then deposits on the surface of the nitrogen-doped carbon nanosheets.

[0053] The molybdenum-sulfur source is heat-treated at 800°C to decompose into nano-molybdenum disulfide. Hydrazine is used as a reducing agent to cause the molybdenum-sulfur source to release a large amount of ammonia, thereby forming nano-molybdenum disulfide with a fullerene-like structure.

[0054] Furthermore, the usage ratio of molybdenum-sulfur source, N-methyl-2-pyrrolidone, hydrazine, and nitrogen-doped carbon nanosheets is (1.2-1.3) g: (35-45) mL: (0.1-0.3) mL: (0.2-0.3) g.

[0055] B3. Add graphene oxide and modified nitrogen-doped carbon nanosheets to deionized water, ultrasonically treat for 10 min, filter, wash with deionized water three times, and dry in an oven at 80°C for 10 min to obtain a composite layered nanomaterial.

[0056] Among them, the gaps between the graphene oxide nanosheets are abundant. After ultrasonic treatment, the modified nitrogen-doped carbon nanosheets are intercalated into the graphene oxide layers to form a composite layered nanomaterial, which increases the thickness of the lubricating film between the roller and the steel billet. Through the slip between the composite layered nanomaterials, the shear force at the interface is effectively reduced, providing a better lubrication effect.

[0057] Furthermore, the usage ratio of graphene oxide, modified nitrogen-doped carbon nanosheets, and deionized water is (0.2-0.26) g:(1-1.4) g:(80-120) mL.

[0058] Further, the nitrogen-carbon precursor is specifically prepared by the following steps:

[0059] A 5.6 mmol / L copper chloride aqueous solution, 4,4'-bipyridine and ethanol were mixed and allowed to stand for 7 days to obtain a precipitate, which was filtered and dried in an oven at 80° C. for 10 minutes to obtain a nitrogen-carbon precursor.

[0060] Furthermore, the usage ratio of copper chloride aqueous solution, 4,4'-bipyridine and ethanol is (80-100) mL:(0.06-0.1) g:(8-12) mL.

[0061] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) In the technical scheme of the present invention, nano-nickel particles are synthesized on the surface of nano-silicon carbide, and then a concave-convex structure is formed on the surface of nano-silicon carbide, thereby increasing the contact area between the nano-silicon carbide and the steel material, so that the reinforcing filler formed by the nano-silicon carbide particles can be evenly dispersed in the molten steel, and the steel matrix can penetrate into the gaps between the concave-convex structure on the surface of the nano-silicon carbide in the reinforcing filler, thereby improving the bonding force between the reinforcing filler formed by the nano-silicon carbide particles and the steel matrix, thereby forming a dense steel material and improving the toughness and mechanical properties of the steel material; modified nano-silicon carbide is deposited on the surface of carbon fiber to block the pores on the surface of the carbon fiber, reducing the contact area between the carbon fiber and oxygen, and the excellent aspect ratio of the carbon fiber has good fluidity, which is inserted into the pores of the steel material to improve the density, and can also enhance the dispersion of the nano-silicon carbide loaded with nano-nickel particles in the steel matrix. In addition, the carbon fiber can hinder the dislocation movement of the steel material and improve the strength of the steel material.

[0063] (2) In the technical scheme of the present invention, 4,4'-bipyridine and cupric chloride form a copper-pyridine complex as a nitrogen-carbon precursor, and the formed nitrogen-doped carbon nanosheets serve as nano-additives for water-based nano-lubricants, which can form a nano-lubricating film on the surface of the roller, provide a better lubrication effect, and reduce the friction loss of the steel billet during the rolling process; fullerene-like nano-molybdenum disulfide is synthesized on the surface of the nitrogen-doped carbon nanosheets, which, on the one hand, blocks the porous structure of the nitrogen-doped carbon nanosheets, improves the density of the nitrogen-doped carbon nanosheets, and thus improves the compressive strength, and avoids the porous structure being brittle and causing breakage during the rolling process; on the other hand, spherical nano-molybdenum disulfide is formed on the surface of the nitrogen-doped carbon nanosheets, producing a rolling lubrication effect, reducing the friction between the steel billet and the rolling mill components during the rolling process, having a better lubrication effect, and thus reducing the wear of the rollers.

[0064] (3) In the technical solution of the present invention, the modified nitrogen-doped carbon nanosheets are intercalated between the graphene oxide layers to form a composite layered nanomaterial, which increases the thickness of the lubricating film between the rollers and the steel billet. The shear force at the interface is effectively reduced through the slip between the composite layered nanomaterials, providing a better lubrication effect. In addition, the graphene oxide is coated on the upper and lower surfaces of the modified nitrogen-doped carbon nanosheets, providing a stable slip space for the spherical nano-molybdenum disulfide on the surface of the modified nitrogen-doped carbon nanosheets, thereby avoiding the spherical nano-molybdenum disulfide from peeling off from the nitrogen-doped carbon nanosheets during the friction process, resulting in an increase in friction and affecting the lubrication effect. In addition, the formed composite layered nanomaterial has good compressive resistance, and its layered structure can absorb the stress generated during the rolling process, thereby avoiding damage to the nano-lubricating material caused by rolling.

[0065] (4) In the technical solution of the present invention, the composite layered nanomaterial is mixed with phytic acid and mercaptosilane, and the hydroxyl groups generated by the hydrolysis of phytic acid and mercaptosilane react to form a cross-linked network structure, and the composite layered nanomaterial is embedded in the cross-linked network structure, thereby improving the water solubility of the composite layered nanomaterial and avoiding the agglomeration of the composite layered nanomaterial in the water-based system. In addition, the phosphorus hydroxyl groups and mercapto groups contained in the cross-linked network structure can complex with the iron ions in the iron oxide sheets easily generated by oxidation on the surface of the rolling mill, thereby reducing the formation of iron oxide and avoiding the formed iron oxide scale adhering to the surface of the rolling mill and being pressed into the steel billet, thereby affecting the quality of the rolled steel bar. In addition, the complex formed by complexing with the iron ions can improve the bonding force between the composite layered nanomaterial and the rolling mill. DETAILED DESCRIPTION

[0066] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] The raw materials used in the embodiments of the present invention are as follows: copper chloride (chemically pure, Sinopharm Chemical Reagent Co., Ltd.); 4,4'-bipyridine (Shanghai Anaiji Chemical Co., Ltd.); dopamine (chemically pure, Shanghai Aladdin Biochemical Technology Co., Ltd.); nickel nitrate hexahydrate (analytical pure, Tianjin Damao Chemical Reagent Factory); ammonium tetrathiomolybdate (Beijing Bailingwei Technology Co., Ltd.); hydrazine, N-methyl-2-pyrrolidone (Beijing Bailingwei Technology Co., Ltd.); phytic acid (purity 90%, Shanghai Xushuo Biotechnology Co., Ltd.); 3-mercaptopropyltrimethoxysilane (purity 97%, Shanghai MacLean Biochemical Technology Co., Ltd.); sodium dodecylbenzenesulfonate (purity 90%, Guangdong Yunxing Biotechnology Co., Ltd.); glycerol (purity 99.7%, Shandong Jinan Huifengda Chemical Co., Ltd.).

[0068] The particle size of nano-silicon carbide is 40-60nm, from MacLean Reagent Company.

[0069] The diameter of carbon fiber is 0.1-2μm, and the diameter is 30-50nm, Jiangsu Shunju Carbon Fiber Products Co., Ltd.

[0070] The particle size of graphene oxide is 100-200nm, Tianjin Rayleigh Optoelectronics Technology Co., Ltd.

[0071] The nitrogen-carbon precursor is specifically prepared by the following steps:

[0072] 90 mL of 5.6 mmol / L copper chloride aqueous solution, 0.08 g of 4,4'-bipyridine and 10 mL of ethanol were mixed and allowed to stand for 7 days to obtain a precipitate, which was filtered and dried in an oven at 80° C. for 10 min to obtain a nitrogen-carbon precursor.

[0073] Example 1

[0074] The reinforcing filler is specifically prepared by the following steps:

[0075] A1. Add 0.5 g of nano-silicon carbide to 45 mL of Tris-HCl buffer solution with a pH of 8, stir evenly, add 0.3 g of dopamine, stir at room temperature for 3 h, filter, wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain pretreated nano-silicon carbide.

[0076] A2. Add 1.6 g of nickel nitrate hexahydrate to 50 mL of ethanol, stir evenly, add 0.3 g of pretreated nano-silicon carbide, stir at 25°C for 10 min, stir at 75°C to remove ethanol, dry in an oven at 70°C for 10 min, place in a tubular furnace, heat to 500°C, pass 20% argon-hydrogen mixed gas, perform thermal reduction for 2 h, cool to room temperature, and obtain modified nano-silicon carbide.

[0077] A3. Place 0.5 g of carbon fiber in 30 mL of 58% nitric acid aqueous solution, stir at 60°C for 1 h, take out, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain pretreated carbon fiber. Add 0.2 g of modified nano-silicon carbide and 0.45 g of γ-aminopropyltriethoxysilane to 12 mL of ethanol and 2 mL of deionized water, stir evenly, add 0.2 mL of 36% hydrochloric acid to adjust the pH to 4, stir and react at 40°C for 10 min, add 0.4 g of pretreated carbon fiber, continue to react for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain reinforcing filler.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that nano-nickel is not synthesized on the pretreated nano-silicon carbide surface, and the remaining steps and raw materials are the same as those of Example 1.

[0080] A1. Add 0.5 g of nano-silicon carbide to 45 mL of Tris-HCl buffer solution with a pH of 8, stir evenly, add 0.3 g of dopamine, stir at room temperature for 3 h, filter, wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain pretreated nano-silicon carbide.

[0081] A2. Place 0.5 g of carbon fiber in 30 mL of 58% nitric acid aqueous solution, stir at 60 ° C for 1 h, take out, wash with deionized water 3 times, and dry in a 70 ° C oven for 10 min to obtain pretreated carbon fiber. Add 0.2 g of pretreated nano-silicon carbide and 0.45 g of γ-aminopropyltriethoxysilane to 12 mL of ethanol and 2 mL of deionized water, stir evenly, add 0.2 mL of 36% hydrochloric acid to adjust the pH to 4, stir and react at 40 ° C for 10 min, add 0.4 g of pretreated carbon fiber, continue to react for 10 min, filter, wash with deionized water 3 times, and dry in a 70 ° C oven for 10 min to obtain reinforcing filler.

[0082] Example 2

[0083] The water-based nano-lubricant is specifically prepared by the following steps:

[0084] B1. Place 5 g of nitrogen-carbon precursor in a carbonization furnace, carbonize at 500°C for 1 h, cool to room temperature, take out, soak in 50 mL of 4 mol / L nitric acid for 24 h, filter, wash with deionized water 3 times, and dry in an oven at 40°C for 1 h to obtain nitrogen-doped carbon nanosheets.

[0085] B2. Add 1.25 g of ammonium tetrathiomolybdate to 40 mL of N-methyl-2-pyrrolidone, stir evenly, heat to 80°C, stir for 2 h, add 0.2 mL of hydrazine, continue stirring for 1 h, add 0.25 g of nitrogen-doped carbon nanosheets, stir evenly, apply negative pressure at -0.1 MPa to allow the precursor to penetrate into the porous nanomaterial, soak for 10 h, place in an 80°C oven to dry for 8 h to evaporate the solvent, place in a tubular furnace at 800°C, pass nitrogen, heat treat for 2 h, and cool to room temperature to obtain modified nitrogen-doped carbon nanosheets.

[0086] B3. Add 0.23 g of graphene oxide and 1.2 g of modified nitrogen-doped carbon nanosheets into 100 mL of deionized water, ultrasonically treat for 10 min, filter, wash with deionized water three times, and dry in an oven at 80 °C for 10 min to obtain a composite layered nanomaterial.

[0087] B4. Add 3.2 mL of phytic acid and 2 mL of 3-mercaptopropyltrimethoxysilane to 100 mL of deionized water, stir and react at 50°C for 30 minutes, add 1.5 g of composite layered nanomaterial, continue stirring for 10 minutes, filter, and dry in an oven at 80°C for 10 minutes to obtain a nano-lubricating filler; mix 3 g of nano-lubricating filler, 11 g of glycerol, 0.25 g of sodium dodecylbenzene sulfonate, and 100 g of deionized water, stir evenly, and obtain a water-based nano-lubricant.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 2 is that nano-molybdenum disulfide is not synthesized on the surface of the nitrogen-doped carbon nanosheets, and the remaining steps are synchronized with Example 2.

[0090] B1. Place 5 g of nitrogen-carbon precursor in a carbonization furnace, carbonize at 500°C for 1 h, cool to room temperature, take out, soak in 50 mL of 4 mol / L nitric acid for 24 h, filter, wash with deionized water 3 times, and dry in an oven at 40°C for 1 h to obtain nitrogen-doped carbon nanosheets.

[0091] B2. 0.23 g of graphene oxide and 1.2 g of nitrogen-doped carbon nanosheets were added to 100 mL of deionized water, ultrasonically treated for 10 min, filtered, washed with deionized water three times, and dried in an oven at 80 °C for 10 min to obtain a composite layered nanomaterial.

[0092] B3. Add 3.2 mL of phytic acid and 2 mL of 3-mercaptopropyltrimethoxysilane to 100 mL of deionized water, stir and react at 50°C for 30 minutes, add 1.5 g of composite layered nanomaterial, continue stirring for 10 minutes, filter, and dry in an oven at 80°C for 10 minutes to obtain a nano-lubricating filler; mix 3 g of nano-lubricating filler, 11 g of glycerol, 0.25 g of sodium dodecylbenzene sulfonate, and 100 g of deionized water, stir evenly, and obtain a water-based nano-lubricant.

[0093] Comparative Example 3

[0094] The difference between this comparative example and Example 2 is that graphene oxide is not added, and the remaining steps are synchronized with Example 2.

[0095] B1. Place 5 g of nitrogen-carbon precursor in a carbonization furnace, carbonize at 500°C for 1 h, cool to room temperature, take out, soak in 50 mL of 4 mol / L nitric acid for 24 h, filter, wash with deionized water 3 times, and dry in an oven at 40°C for 1 h to obtain nitrogen-doped carbon nanosheets.

[0096] B2. Add 1.25g of ammonium tetrathiomolybdate, a molybdenum-sulfur source, to 40mL of N-methyl-2-pyrrolidone, stir evenly, heat to 80°C, stir for 2h, add 0.2mL of hydrazine, continue stirring for 1h, add 0.25g of nitrogen-doped carbon nanosheets, stir evenly, apply negative pressure at -0.1MPa to allow the precursor to penetrate into the porous nanomaterial, soak for 10h, place in an 80°C oven to dry for 8h to evaporate the solvent, place in a tubular furnace at 800°C, pass nitrogen, heat treat for 2h, cool to room temperature, and obtain modified nitrogen-doped carbon nanosheets.

[0097] B3. Add 3.2 mL of phytic acid and 2 mL of 3-mercaptopropyltrimethoxysilane to 100 mL of deionized water, stir and react at 50°C for 30 min, add 1.5 g of modified nitrogen-doped carbon nanosheets, continue stirring for 10 min, filter, and dry in an oven at 80°C for 10 min to obtain a nano-lubricating filler; mix 3 g of nano-lubricating filler, 11 g of glycerol, 0.25 g of sodium dodecylbenzene sulfonate, and 100 g of deionized water, stir evenly, and obtain a water-based nano-lubricant.

[0098] Comparative Example 4

[0099] The difference between this comparative example and Example 2 is that phytic acid and 3-mercaptopropyltrimethoxysilane are not added, and the remaining steps are synchronized with Example 2.

[0100] B1. Place 5 g of nitrogen-carbon precursor in a carbonization furnace, carbonize at 500°C for 1 h, cool to room temperature, take out, soak in 50 mL of 4 mol / L nitric acid for 24 h, filter, wash with deionized water 3 times, and dry in an oven at 40°C for 1 h to obtain nitrogen-doped carbon nanosheets.

[0101] B2. Add 1.25 g of ammonium tetrathiomolybdate to 40 mL of N-methyl-2-pyrrolidone, stir evenly, heat to 80°C, stir for 2 h, add 0.2 mL of hydrazine, continue stirring for 1 h, add 0.25 g of nitrogen-doped carbon nanosheets, stir evenly, apply negative pressure at -0.1 MPa to allow the precursor to penetrate into the porous nanomaterial, soak for 10 h, place in an 80°C oven to dry for 8 h to evaporate the solvent, place in a tubular furnace at 800°C, pass nitrogen, heat treat for 2 h, and cool to room temperature to obtain modified nitrogen-doped carbon nanosheets.

[0102] B3. Add 0.23 g of graphene oxide and 1.2 g of modified nitrogen-doped carbon nanosheets into 100 mL of deionized water, ultrasonically treat for 10 min, filter, wash with deionized water three times, and dry in an oven at 80 °C for 10 min to obtain a composite layered nanomaterial.

[0103] B4. Mix 3 g of the composite layered nanomaterial, 11 g of glycerol, 0.25 g of sodium dodecylbenzene sulfonate, and 100 g of deionized water, and stir evenly to obtain a water-based nanolubricant.

[0104] Example 3

[0105] A high-precision rolling process for rolled steel bars comprises the following steps:

[0106] S1. 90 g of steel component raw material and 0.8 g of the reinforcing filler prepared in Example 1 are mixed, smelted into molten iron, refined, and cast into a steel billet, wherein the smelting temperature is 1260° C., the smelting time is 4 h, the pouring temperature is 1000° C., and the pouring time is 2.5 h.

[0107] The steel component raw materials include 0.22% carbon, 0.22% silicon, 1.4% manganese, 0.02% chromium, 0.006% molybdenum, 0.007% nickel and the balance is iron and inevitable impurities.

[0108] S2. Place the steel billet in a hot rolling mill, spray the water-based nanolubricant prepared in Example 2, and obtain a rolled steel bar after hot rolling treatment, wherein the spraying temperature is 135°C, the spraying time is 1.5 min, the hot rolling mill is selected from a two-roll experimental hot rolling mill, and the diameter of the two rolls is 225×254 mm; the hot rolling treatment temperature is 850°C, the hot rolling speed is 0.45 m / s, and the hot rolling pressure is 90N.

[0109] Example 4

[0110] A high-precision rolling process for rolled steel bars comprises the following steps:

[0111] S1. 95 g of steel component raw material and 0.9 g of the reinforcing filler prepared in Example 1 are mixed, smelted into molten iron, refined, and cast into a steel billet, wherein the smelting temperature is 1260° C., the smelting time is 4 h, the pouring temperature is 1000° C., and the pouring time is 2.5 h.

[0112] The steel component raw materials include 0.25% carbon, 0.23% silicon, 1.45% manganese, 0.025% chromium, 0.007% molybdenum, 0.008% nickel and the balance is iron and inevitable impurities.

[0113] S2. Place the steel billet in a hot rolling mill, spray the water-based nanolubricant prepared in Example 2, and obtain a rolled steel bar after hot rolling treatment, wherein the spraying temperature is 135°C, the spraying time is 1.5 min, the hot rolling mill is selected from a two-roll experimental hot rolling mill, and the diameter of the two rolls is 225×254 mm; the hot rolling treatment temperature is 850°C, and the hot rolling speed is 0.45 m / s.

[0114] Example 5

[0115] A high-precision rolling process for rolled steel bars comprises the following steps:

[0116] S1. 100 g of steel component raw material and 1 g of reinforcing filler prepared in Example 1 are mixed, smelted into molten iron, refined, and cast into a steel billet, wherein the smelting temperature is 1260° C., the smelting time is 4 h, the pouring temperature is 1000° C., and the pouring time is 2.5 h.

[0117] The steel component raw materials include 0.27% carbon, 0.25% silicon, 1.5% manganese, 0.03% chromium, 0.008% molybdenum, 0.009% nickel and the balance is iron and inevitable impurities.

[0118] S2. Place the steel billet in a hot rolling mill, spray the water-based nanolubricant prepared in Example 2, and obtain a rolled steel bar after hot rolling treatment, wherein the spraying temperature is 135°C, the spraying time is 1.5 min, the hot rolling mill is selected from a two-roll experimental hot rolling mill, and the diameter of the two rolls is 225×254 mm; the hot rolling treatment temperature is 850°C, the hot rolling speed is 0.45 m / s, and the hot rolling pressure is 90N.

[0119] Comparative Example 5

[0120] The difference between this comparative example and Example 4 is that the reinforcing filler is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.

[0121] Comparative Example 6

[0122] The difference between this comparative example and Example 4 is that the water-based nanolubricant is replaced by the substance prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.

[0123] Comparative Example 7

[0124] The difference between this comparative example and Example 4 is that the water-based nanolubricant is replaced by the substance prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.

[0125] Comparative Example 8

[0126] The difference between this comparative example and Example 4 is that the water-based nanolubricant is replaced by the substance prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.

[0127] The performance of the rolled steel bars prepared in Examples 3-5 and Comparative Examples 5-8 was tested;

[0128] Mechanical properties: The rolled steel bars prepared above were tested on a universal testing machine of model WDW-100G at a tensile rate of 10 -3 m / s, and a Y10 / 5 axial extensometer was used to monitor the initial strain during loading and record the tensile strength.

[0129] The friction performance of the water-based nano-lubricant prepared above was tested using an MRS-10A four-ball friction tester; the hot rolling pressure of the hot rolling mill in Examples 3-5 and Comparative Examples 5-8 was recorded, the rolling pressure during the rolling process was detected, and the roll consumption was tested; after the 90N rolling was completed, the film formation phenomenon on the surface of the hot rolling mill roll in Examples 3-5 and Comparative Examples 5-8 was observed;

[0130] The test results are shown in Table 1 below.

[0131] Table 1: Test results

[0132]

[0133] It can be seen from the test results in Table 1 that in Comparative Example 5, nano-nickel was not synthesized on the surface of pretreated nano-silicon carbide to prepare a reinforcing filler, and when it was added to the rolled steel bar, its mechanical properties decreased. This is because nano-nickel was synthesized on the surface of pretreated nano-silicon carbide to form a concave-convex structure, which can increase the contact area with the steel material, and the steel matrix can penetrate into the gaps of the concave-convex structure on the surface of the nano-silicon carbide, thereby improving the bonding force between the nano-silicon carbide and the steel matrix, and thus enhancing the mechanical properties of the steel material. However, the surface of the pretreated nano-silicon carbide lacks nano-nickel, and this effect cannot be achieved, so the mechanical properties decrease; Comparative Example 6 does not synthesize nano-nickel on the surface of the nitrogen-doped carbon nanosheet Molybdenum sulfide, the water-based nano-lubricant prepared is sprayed on the hot rolling mill, and the lubricity between the steel billet and the rolled steel decreases, and the pressure of the hot rolling mill increases, and the thickness distribution of the adsorption film on the surface of the rolled steel is uneven. This is because the nano-molybdenum disulfide with a fullerene structure synthesized on the surface of the nitrogen-doped carbon nanosheet can block the porous structure of the nitrogen-doped carbon nanosheet, improve the density of the nitrogen-doped carbon nanosheet, and the spherical nano-molybdenum disulfide formed can produce a rolling lubrication effect, reduce the friction between the steel billet and the rolling mill components during the rolling process, and have a good lubrication effect. However, the surface of the nitrogen-doped carbon nanosheet lacks nano-molybdenum disulfide, and this effect cannot be achieved, so the mechanical properties are reduced;

[0134] In Comparative Example 7, graphene oxide was not added, and the prepared water-based nano-lubricant was sprayed on the hot rolling mill. The lubricity between the steel billet and the rolled steel decreased, and the pressure of the hot rolling mill increased, and the film formation on the rolled steel surface was poor. This is because graphene oxide was coated on the upper and lower surfaces of the modified nitrogen-doped carbon nanosheets, providing a stable sliding space for the spherical nano-molybdenum disulfide on the surface of the modified nitrogen-doped carbon nanosheets, avoiding the spherical nano-molybdenum disulfide from peeling off from the nitrogen-doped carbon nanosheets during the friction process, resulting in increased friction and affecting the lubrication effect; in Comparative Example 8, phytic acid and 3-mercaptopropyltrimethoxysilane were not added, When the prepared water-based nanolubricant is sprayed on a hot rolling mill, the lubricity between the steel billet and the rolled steel decreases, and the mechanical properties of the rolled steel material decrease. This is because the phytic acid and mercaptosilane are mixed to form a cross-linked network structure, which can complex with the iron ions in the iron oxide flakes produced by the easy oxidation of the roller surface, reduce the formation of iron oxide, and prevent the formed iron oxide scale from adhering to the roller surface and being pressed into the steel billet, affecting the quality of the rolled steel bar. Without the addition of phytic acid and 3-mercaptopropyltrimethoxysilane, this effect cannot be achieved. Therefore, the lubricity between the steel billet and the rolled steel decreases, and the mechanical properties of the rolled steel material decrease.

[0135] The data in Table 1 show that the rolled steel bars prepared in Examples 3-5 meet the test performance requirements, while the rolled steel bars prepared in Comparative Examples 5-8 do not meet the performance requirements. This indicates that the rolled steel bars prepared in the present invention have good mechanical properties, low rolling energy consumption, and the rolled steel bars have high quality.

[0136] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0137] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-precision rolling process for rolled steel bars, characterized in that: The following steps are involved: S1. The steel component raw materials and reinforcing fillers are mixed, smelted into molten iron, and then refined and cast into billets; The reinforcing filler is prepared by mixing nano silicon carbide and a nickel source, performing a heating reduction reaction, and then depositing the mixture onto the surface of the carbon fiber. S2. placing the steel billet in a hot rolling mill, spraying a water-based nano-lubricant, and hot rolling to obtain a rolled steel bar; The water-based nano-lubricant comprises the following raw materials in parts by weight: 2-4 parts of nano-lubricating filler, 10-12 parts of glycerol, 0.2-0.3 parts of sodium dodecylbenzene sulfonate, and 80-120 parts of deionized water; The nano lubricating filler is prepared by mixing a composite layered nano material, phytic acid and mercaptosilane and stirring the mixture for reaction; The composite layered nanomaterial is prepared by mixing nitrogen-doped carbon nanosheets with a molybdenum-sulfur source, heat-treating the mixture, and then mixing it with graphene oxide; The nitrogen-doped carbon nanosheet is prepared by carbonizing a nitrogen-carbon precursor and etching with nitric acid.

2. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The nickel source is selected from nickel nitrate hexahydrate or nickel chloride; the thermal reduction reaction temperature is 450-500° C., and the thermal reduction reaction time is 1-3 hours.

3. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The water-based nano-lubricant is specifically prepared by the following steps: mixing nano-lubricating filler, glycerol, sodium dodecylbenzene sulfonate and deionized water, and stirring evenly to obtain the water-based nano-lubricant.

4. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The nitrogen-carbon precursor is specifically prepared by the following steps: mixing a 5.6 mmol / L copper chloride aqueous solution, 4,4'-bipyridine and ethanol, standing for 7 days to obtain a precipitate, filtering it, and drying it in an oven at 80° C. for 10 minutes to obtain a nitrogen-carbon precursor.

5. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The nitric acid concentration is 3-5 mol / L.

6. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The molybdenum-sulfur source is selected from ammonium tetrathiomolybdate; the heat treatment temperature is 750-850° C., and the heat treatment time is 1-3 hours.

7. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The steel component raw material contains 0.22-0.27% carbon, 0.22-0.25% silicon, 1.4-1.5% manganese, 0.02-0.03% chromium, 0.006-0.008% molybdenum, 0.007-0.009% nickel and the balance is iron and inevitable impurities.

8. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The mass ratio of the steel component raw material to the reinforcing filler is (90-100):(0.8-1).

9. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The smelting temperature is 1200-1280° C., the pouring temperature is 800-1050° C., and the pouring time is 2-3 hours.

10. A high-precision rolling process for rolled steel bars according to claim 1, characterized in that: The hot rolling mill is selected from a two-roll experimental hot rolling mill, the diameter of the two rolls is 225-254 mm; the hot rolling treatment temperature is 800-900° C., and the hot rolling speed is 0.3-0.6 m / s.

Citation Information

Patent Citations

  • Silicon carbide nanowire / carbon fiber cloth composite material and preparation method and application thereof

    CN109126846A

  • Woven carbon fiber reinforced steel matrix composite

    CN111719092A